Determinants of Stunting in Children Under Five - Fikitri Marya Sari; Wulandari Wulandari; Danur Azissah Roeliana Sofais; Novega Novega; Ravika Ramlis; Yusran Fauzi; Bintang Agustina Pratiwi; Agung Sutriyawan (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Stunting in children under five years old remains a major global health concern, affecting approximately 22.3% of children worldwide. It contributes to impairments in physical and cognitive development, reduced academic performance, lower economic productivity, and increased susceptibility to non-communicable diseases. This study aims to synthesize comprehensive evidence regarding the determinants associated with stunting in children under five. Methods: A systematic review and meta-analysis were conducted using data from 22 eligible studies retrieved from international databases (Scopus, PubMed, ScienceDirect, and Springer). Heterogeneity was assessed using the I² statistic, and a random-effects model was applied to estimate the odds ratio (OR) and 95% confidence interval (CI). Publication bias was evaluated using funnel plot visualization and Egger’s test. Results: Meta-analysis findings demonstrate that several determinants significantly increase the risk of stunting, including low maternal education (OR = 1.63; 95% CI: 1.11–2.41; I² = 84.64%), low paternal education (OR = 1.66; 95% CI: 1.05-2.61; I² = 55.64%), maternal occupation (OR = 1.59; 95% CI: 1.09-2.32; I² = 71.16%), low household income (OR = 1.83; 95% CI: 1.30-2.58; I² = 73.72%), and households with two or more young children (OR = 2.34; 95% CI: 1.65-3.30; I² = 23.89%). Additional factors such as inadequate antenatal care (OR = 1.62; 95% CI: 1.07-2.47; I² = 41.71%), non-exclusive breastfeeding (OR = 1.21; 95% CI: 1.60-3.03; I² = 80.25%), incomplete immunization (OR = 2.77; 95% CI: 1.48-5.19; I² = 63.58%), low birth weight (OR = 2.72; 95% CI: 1.61-4.66; I² = 65.71%), and a history of infectious diseases (OR = 1.96; 95% CI: 1.36-2.82; I² = 64.06%) were also strongly associated with stunting. No substantial publication bias was indicated by Egger’s test (p > 0.05). Conclusion:Stunting is influenced by a combination of sociodemographic factors and maternal-child health services, such as parental education, household income, and exclusive breastfeeding. Reducing the prevalence of stunting requires integrated policies that encompass education, health, and family economic empowerment.